Awareness and Utilization Pattern of Unani Medicine in India: A Systematic Review - Asim Ali Khan; Aanchal Anant Awasthi; Shazina Saeed; Shagufta Parveen; Jugal Kishore; Rajiv Janardhanan; W Selvamurthy (Tehran University of Medical Sciences, 2022)
Unani medicine is one of the traditional medical systems in India that is practiced and taught in an organized manner. While going through the literature, it has been observed that in the past, not many efforts have been made to understand the awareness level and utilization pattern among the population. This systematic review was conducted to better understand the awareness and utilization pattern of Unani medicine in India. Using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guideline, the results of survey-based studies conducted about the awareness and utilization pattern of Unani medicine in India were systematically reviewed. Thirteen studies conducted on awareness or utilization patterns, which exclusively represented data on Unani medicine and not Ayurveda, Yoga, Naturopathy, Unani, Siddha and Homeopathy (AYUSH) in general, were included in the present systematic review. A wide variation regarding awareness of Unani medicine is observed, ranging from 28.9% to 100% in different populations. Only five studies reported utilization patterns, which also varied considerably (13.8% to 74%). Unani Medicine is generally used in musculoskeletal disorders (20%-60.2%) and skin disorders (21.1%-64.9%). On the other hand, fifty-seven papers on surveys of CAM and AYUSH were found regarding utilization and consumption patterns. The findings demonstrate that thirteen papers entirely focused on the Unani System of Medicine. Henceforth, the awareness of the Unani system of Medicine has not been reported among the masses, and to provide its maximum benefits, certain strategies need to be formulated.